Big mushy happy lump : a "Sarah's Scribbles" collection - Andersen, Sarah (Sarah C.) (Andrews McMeel Publishing, 2017)
Containing illustrated personal essays on the author's real-life experiences with anxiety, career, relationships and other adulthood challenges, this collection of the hugely popular, world-famous Sarah's Scribbles comics are perfect for those of us who boast bookstore-ready bodies and Netflix-ready hair.